2021
DOI: 10.5468/ogs.21123
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNAs as biomarkers of cervical carcinogenesis: a systematic review

Abstract: We performed a systematic review to identify the role of microRNAs (miRNAs) as biomarkers in the progression of cervical precancerous lesions. A comprehensive search of the Cochrane Controlled Register of Trials, PubMed, ScienceDirect, and Embase databases was performed for articles published between January 2010 and June 2020. The following Medical Subject Headings (MeSH) terms were searched: “microRNA” and “cervical” and “lesion.” All study designs that aimed to evaluate the correlation of miRNA expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Our review found out a number of microRNAs that are either down regulated or up regulated in CIN or cervical cancer. We report many more microRNAs that are down regulated in CIN or cervical cancer compared to a previous systematic review by Nagandla et al ( Nagandla et al, 2021 ) who reported only five microRNAs (miR-34, miR-7, miR-203, miR-29 and miR-375) as down regulated in CIN and cervical cancer. In their systematic review, Pardini et al ( Pardini et al, 2018 ) indicated miR-125b, miR-375, miR-100 and miR-145 as down regulated.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Our review found out a number of microRNAs that are either down regulated or up regulated in CIN or cervical cancer. We report many more microRNAs that are down regulated in CIN or cervical cancer compared to a previous systematic review by Nagandla et al ( Nagandla et al, 2021 ) who reported only five microRNAs (miR-34, miR-7, miR-203, miR-29 and miR-375) as down regulated in CIN and cervical cancer. In their systematic review, Pardini et al ( Pardini et al, 2018 ) indicated miR-125b, miR-375, miR-100 and miR-145 as down regulated.…”
Section: Discussioncontrasting
confidence: 53%
“…In their systematic review, Pardini et al ( Pardini et al, 2018 ) indicated miR-125b, miR-375, miR-100 and miR-145 as down regulated. Notable is the up regulation of miR-21 as reported by Nagandla et al ( Nagandla et al, 2021 ) though in exfoliated cervical cells. Also, in a previous systematic review by Pardini et al ( Pardini et al, 2018 ) the notable microRNAs that were indicated as up regulated included miR-9, miR-196a and miR-21.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…E7 can also enhance E6-induced telomerase activation by increasing hTERT expression ( 31 ). At present, a large number of dysregulated genes are identified in HPV-CCa ( 32 34 ). However, most studies focused on the differentially expressed genes between normal and CCa tissues, and molecular alterations spanning from HPV infection, to CIN and CCa, have rarely been investigated.…”
Section: Discussionmentioning
confidence: 99%